P6.034 Potential Impact of a Provincial Electronic Health Records on STI/HIV Testing at STI Clinics. (13th July 2013) - Ogilvie, G; Taylor, D; Gilbert, M; Achen, M; Lester, R
Abstract : Background: Clients who choose to attend sexually transmitted diseases clinics for care express a desire for anonymity and non-judgmental care. We surveyed a convenience sample of clients attending the BC Centre for Disease Control (BCCDC) Provincial STI clinic to assess the acceptability of electronic health records (EHR) containing sensitive sexual health information which may be available to healthcare professionals external to the BCCDC STI clinic. Methods: All clients attending the BCCDC STI clinic between July-October 2012 were offered a 16-item questionnaire to determine if it was acceptable for their sexual health information to be made available to their family physician, pharmacist, medical specialist, and nurses at other STI clinics through the provincial EHR. Demographic information was also collected. Frequency analysis was conducted using SPSS-14 Results: At total of 378 (227 [60%] male) individuals completed the survey. Seventy-four percent were 19–39 years old (range 14yrs - > 59yrs). Sixty-seven percent (n = 254) were Caucasian and 55% (n = 209) had a university degree. The majority (86%) of respondents stated they were satisfied with the current computer health record with closed access to external healthcare professionals. One hundred and one (27%) respondents stated it would not be acceptable for their family physician (n = 101 [27%]), pharmacist (n = 197 [52%]), medical specialist (n = 106 [28%]), and nurses in other STI clinics (n = 112 [30%]) to have access their BCCDC STI clinic record. 133 respondents (30%) stating they would be less likely to get tested for HIV and STIs and if their BCCDC STI clinic record were made available as part of the provincial EHR. Conclusion: The introduction of a provincial EHR for STI/HIV care information is not acceptable to a significant proportion of clients and may result in reduced screening, posing a threat to the control of sexually transmitted infections in British Columbia. Further monitoring and safeguards should be considered.